2009
DOI: 10.1016/j.bandl.2008.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Language proficiency and executive control in proactive interference: Evidence from monolingual and bilingual children and adults

Abstract: Two studies are reported in which monolingual and bilingual children (Study 1) and adults (Study 2) completed a memory task involving proactive interference. In both cases, the bilinguals attained lower scores on a vocabulary test than monolinguals but performed the same on the proactive interference task. For the children, bilinguals made fewer intrusions from previous lists even though they recalled the same number of words. For the adults, bilinguals recalled more words than monolinguals when the scores wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(145 citation statements)
references
References 42 publications
6
132
1
6
Order By: Relevance
“…This advantage was attributed to the higher demand for executive control in the letter fluency task relative to the semantic fluency task. Similarly, Bialystok and Feng (2009) showed that, despite lower vocabulary scores, bilinguals performed similarly to monolinguals in a proactive interference task. Moreover, bilinguals made fewer errors than monolinguals indicating better executive control.…”
Section: Discussionmentioning
confidence: 99%
“…This advantage was attributed to the higher demand for executive control in the letter fluency task relative to the semantic fluency task. Similarly, Bialystok and Feng (2009) showed that, despite lower vocabulary scores, bilinguals performed similarly to monolinguals in a proactive interference task. Moreover, bilinguals made fewer errors than monolinguals indicating better executive control.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Bialystok and Feng (2009), where bilingual and monolingual children and adults performed a proactive interference task, a bilingual advantage concerning the control of attention was reported, as bilingual participants performed equally well as monolingual ones, although the former had smaller vocabularies, which should have had a negative effect on their overall performance. Like all of the above-mentioned studies, these findings show that bilinguals surpass monolinguals in terms of executive control.…”
Section: Introductionmentioning
confidence: 99%
“…Celkový obrat v negatívnom chápaní bilingvizmu priniesli Peal a Lambert (1962), ktorí zistili lepšiu inteligenciu v bilingválnej skupine ako v kontrolnej, jednojazyčnej. Po tomto zistení nasleduje nespočetné množstvo výskumov poukazujúcich na pozitívny vplyv bilingvizmu na psychiku jednotlivca (Adi-Japha, Berberich-Artzi, Libnawi, 2010;Bassetti, 2007;Bialystok, 2011;Bialystok, Craik, Klein, & Viswanathan, 2004;Bialystok, Craik, & Luk, 2008;Bialystok & Feng, 2009;Kaushanskaya, Blumenfeld, & Marian, 2011;Kaushanskaya & Marian, 2009;Kessler & Quinn, 1980, 1987Torrance, Wu, Gowan, & Aliotti, 1970), z ktorých väčšina prebehla v prvom jazyku bilingválnych. Je otázne, či by sa kognitívne výhody dvojjazyčnosti preukázali aj v prípade testovania v druhom jazyku simultánnych dvojjazyčných.…”
Section: Bilingvizmusunclassified